2003
DOI: 10.1016/s0304-3991(02)00318-2
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-flight atom probe measurements on Ni3Al and Co3W

Abstract: In this study, a VG FIM100 was taken into operation, consisting of a field-ion microscope (FIM), a time-of-flight atom probe (TOFAP) and an imaging atom probe. A tungsten specimen was used to calibrate the conversion of flight times to m/n values. The resulting relative mass resolution of the TOFAP was calculated to be m/Deltam approximately 500 FWHM. In time-of-flight measurements of homemade boron-doped Ni-rich Ni(3)Al, a so-called ladder diagram was constructed from the evaporation data of a <001> pole. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, the influence of solutes on the structure of such boundaries has not been experimentally identified. To this end, we are currently conducting a high-resolution TEM study on grain boundaries in Al and Al-Mg [27]. Another effect that may contribute to the pinning of special boundaries is solute drag on extrinsic grain boundary dislocations (EGBDs) as reported by Song et al [28], who showed that the dissociation rate of EGBDs in Al alloys is reduced by the addition of Mg.…”
Section: Grain Boundary Motionmentioning
confidence: 99%
“…However, the influence of solutes on the structure of such boundaries has not been experimentally identified. To this end, we are currently conducting a high-resolution TEM study on grain boundaries in Al and Al-Mg [27]. Another effect that may contribute to the pinning of special boundaries is solute drag on extrinsic grain boundary dislocations (EGBDs) as reported by Song et al [28], who showed that the dissociation rate of EGBDs in Al alloys is reduced by the addition of Mg.…”
Section: Grain Boundary Motionmentioning
confidence: 99%